PENGARUH KEPEMIMPINAN MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Pada PT Fastrata Buana Tegal) - Sigit Kusprihanto, 08.05.51.0135; Rijanti, Tristiana (Students Journal of Economic and Management, 2013)
The purpose of this study to analyze the effect of motivational leadership and work environment on employeeperformance PT. Fastrata Buana Tegal. The population in this study were all employees of PT Fastrata Buana Tegal. Inthis study, researchers used the entire population is in a company called the census, becauseThe population is relatively slight, amounting to 128 employees in the sampleThe collected data were analyzed using factor analysis to test the validity of the question items, Cronbach Alpha formulafor Reliability of test, regression analysis, to examine the influence of the independent variable on the dependent variable ttest From the regression equation above, shows that leadership is the dominant factor in influencing positive employeeperformance, whereas the effect of motivation on performance and Work Environment negatife work had no effect onemployee performanceKeywords: Leadership, Motivation, Work Environment and Employee Performance.